Algorithms of Perioperative Management of High-Risk Cardiac Surgery Patients with Coronary Artery Disease and Polymorbidity - Gogayeva, Olena K. (Ukrainian Journal of Cardiovascular Surgery, 2023)
The aim. To analyze the effectiveness of the developed algorithms for the perioperative management of high-risk cardiac surgery patients with coronary artery disease (CAD) and polymorbidity. Materials and methods. We analyzed perioperative management of 354 high-risk cardiac surgery patients with CAD with EuroSCORE II predicted mortality >5%, among which 194 (54.8%) underwent isolated coronary artery bypass grafting, and 160 (45.2%) had surgical myocardial revascularization with accompanying valvular pathology correction or left ventricular postinfarction aneurysm resection. All the patients were discharged after cardiac surgery performed at the Department of Surgical Treatment of CAD of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine in the period from 2009 to 2019. As part of the study, general clinical examinations, electrocardiography, echocardiography, coronary angiography, cardiosurgical treatment were provided, and perioperative patient management protocols were developed and implemented. Results. Based on the conducted detailed analysis, it was established that the success of surgical revascularization of the myocardium depends not only on cardiac factors, but also on the compensation of concomitant diseases, the work of an experienced cardiac team consisting of a cardiologist, an interventionist, an anesthesiologist, a cardiac surgeon, and an intensivist. Treatment and prevention measures should be personalized and aimed at timely response to changes in laboratory and hemodynamic indicators of patients at all stages of their management, as well as stabilization of concomitant diseases. An important point in the preoperative preparation of cardiac surgery patients is verification of concomitant diseases with the aim of their timely compensation. The implemented algorithm for searching for comorbid conditions made it possible to improve the diagnosis of initial disorders of glucose metabolism, abnormal uric acid levels and cerebrovascular disease. Lowering the glucose level according to the developed algorithm of management of patients with impaired glucose metabolism in the perioperative period made it possible to reduce the number of postoperative wound infections by 3.4% and arrhythmological complications by 19.4%. Correction of drug therapy taking into account the glomerular filtration rate made it possible to avoid postoperative hemodialysis. Preventive prescription of therapeutic doses of proton pump inhibitors against the background of dual antiplatelet therapy, according to the developed protocol, led to a decrease in postoperative gastroduodenal complications from 5.1% to 0.3%. Conclusions. Implementation of the system of personalized treatment and preventive management of patients in the perioperative period made it possible to reduce postoperative complications from 16.7% to 4% (p=0.0190).